Conversão catalítica de glicerol com ácido acético para formação de produtos de maior valor agregado - Altino, Felyppe Markus Ribeiro Sobral (2020)
In the last decades, the growing production of biodiesel has been generating huge amounts of glycerol as a co-product. The excess volume of residual glycerol resulted in market saturation, making it necessary to develop new strategies for the destination of the product. Alternative catalysts for glycerol acetals via esterification of glycerol with acetic acid were evaluated. Initially the experimental tests used metal oxides (SnO2, WO3, MoO3, Sb2O3 e o Sb2O5), among the evaluated materials the Sb2O5 was the only one to present catalytic activity superior to without catalyst reaction (blank), reaching 98% conversion in 3 h of reaction at 80°C. The results obtained with Sb2O5 are similar to studies available in the literature, making it interesting to investigate antimony coordination compounds. The catalysts evaluated were SbCl3 and SbCl5 at 40 and 80°C, 1:4 molar ratio (glycerol / AcOH) under constant magnetic stirring (3000 rpm). The gas chromatography (GC) technique assists in the characterization of the products. Both chlorinated catalysts presented satisfactory results, highlighting the SbCl5 that at 80°C reached 100% conversion in the initial 15 min, with selectivity order of 46, 33 and 21% for mono, di and triacetin after 180 min, respectively. Another part of the work dedicated to evaluate the catalytic performance of HCl, the purpose of this study was to compare the kinetics of chlorinated complexes against a genuine Brønsted acid. The results found for SbCl5 were superior to those obtained with HCl, highlighting the higher selectivity achieved for di and triacetin, raising evidence that mechanistic steps may be occurring via acidic acid Lewis interaction.